The Role of Administration in Enhancing the Efficiency of Human Resource Management at the Tax Office - Hasibuan, Gabe Rohana; Ahmad, Afnida Rahma; Harahap, Amin (LPPPIPublishing, 2025)
This study examines the strategic role of administrative functions in enhancing the efficiency of Human Resource Management (HRM) in Indonesian tax offices. Using a descriptive qualitative case study approach, data were collected through interviews, document analysis, and direct observation at two regional tax offices. The findings reveal that structured and digitized administrative systems significantly improve the performance of key HR functions, including recruitment, payroll, training, and employee data management. Efficiency scores in administratively supported environments were consistently higher—averaging 27.9% more—than in settings lacking such support. Notably, digital tools reduced processing time, minimized errors, and strengthened transparency and accountability. The study concludes that administration must be reframed from a support function to a strategic enabler within HRM. Strengthening administrative capacity is essential for improving institutional effectiveness, especially in the public sector context.